(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The transition to renewable energy sources is central to mitigating climate change and fostering sustainable development. This paper evaluates the impact of renewable energy technologies on environmental conservation, economic growth, and societal well-being. Key renewable energy types solar, wind, hydro, and bioenergy are analyzed through the metrics of carbon footprint, energy efficiency, economic viability, and social acceptance. Comparative case studies highlight successful implementations and challenges, providing actionable insights into fostering a sustainable energy future.